Agri-Food By-Products as Ingredients: Exploring Purchase Intentions Among a Sample of Italian Consumers - Maria Di Cairano; Nicola Condelli; Angela Lomonaco; Fernanda Galgano (Foods)
Consumer perceptions of upcycled foods, as well as the determinants of food choices, are still not well understood. The aim of this study was to evaluate the impact of psychological and personal traits on purchase intention (PI) towards upcycled foods of Italian consumers. Additionally, willingness to try (WTT), willingness to buy (WTB), and willingness to pay (WTP) for yogurt, bread, and biscuits made with by-products, namely, hazelnut skin and grape pomace powder, were collected. A web-based survey involving 505 consumers was conducted, and partial least squares structural equation modeling (PLS-SEM) was used to evaluate the model. It resulted that food neophobia and attitude towards upcycled foods had a significant impact on PI. In turn, attitude was affected by food neophobia as well as by objective knowledge about food by-products. Unexpectedly, frugality and environmental concern did not affect PI. WTP was product-specific; when WTP was compared to a reference price, it was higher for the yogurt prototype, followed by the bread and biscuits prototypes. Food neophobia affected WTT, WTB, and WTP. This study contributes to providing new insights into the determinants of consumers’ purchase intention for upcycled foods, which are an emerging category of products.